The Isle of Pines: Texts. - Van Sloetten, Henry Cornelius (Utopian Studies, 2006)
The article presents various versions of the text of the book "The Isle of Pines," by Henry Neville. The book tells the story of how bookkeeper George Pines and four women were stranded on the island and established their own political system. The book consists of a letter from voyager Henry Cornelius Van Sloetten narrating how he discovered the settlers as well as the written accounts of Pines handed down to his descendants detailing the accounts of their stay and progress on the island.